Teaching Geometrical Figures in Waray: The LNU-ILS Experience - Voltaire Q. Oyzon; Cyrene C. Lubio; Jose Ismael Salamia; Lorena M. Ripalda (Intelektual Pustaka Media Utama, 2014)
Waray children are â€œunconsciously shifting from their mother language to English and/or Tagalog in their vocabulary useâ€. English vocabularies are more familiar to Waray educands of today than are the indigenous Waray terms, for instance, for geometrical figures, colors, numbers, etc. Still, â€œit is an ongoing debate of what type of language should be used in the implementation of MTBMLE.â€ Should educators use a Waray that borrows heavily from English and other languages or a Waray that uses exclusively its own indigenous terms and concepts? The researchers formulate a single lesson plan using an inductive method incorporating the Montessori Approach. We have two types of pupils at LNU-ILS: Waray pupils whose language at home is Waray, and Waray pupils who are exposed to English at home.